Machine perfusion of the liver and in vivo animal models: a systematic review of the preclinical research landscape - Liu, Wenjia; Jiang, Decan; Schulz, Mareike; Figueiredo, Constança; Dondossola, Daniele; Meister, Franziska Alexandra; Tihanyi, Dora Krisztina; Mehrabi, Arianeb; Tolba, Rene Hany; Czigány, Zoltán; Ernst, Lisa (PLOS ONE, 2024)
Machine perfusion (MP) is often referred to as one of the most promising advancements in liver transplantation research of the last few decades, with various techniques and modalities being evaluated in preclinical studies using animal models. However, low scientific rigor and subpar reporting standards lead to limited reproducibility and translational potential, hindering progress. This pre-registered systematic review (PROSPERO: CRD42021234667) aimed to provide a thematic overview of the preclinical research landscape on MP in liver transplantation using in vivo transplantation models and to explore methodological and reporting standards, using the ARRIVE (Animal Research: Reporting of In Vivo Experiments) score. In total 56 articles were included. Studies were evenly distributed across Asia, Europe, and the Americas. Porcine models were used in 57.1% of the studies, followed by rats (39.3%) and dogs (3.6%). In terms of graft type, 55.4% of the studies used donation after cardiac death grafts, while donation after brain death grafts accounted for 37.5%. Regarding MP modalities, the distribution was as follows: 41.5% of articles utilized hypothermic MP, 21.5% normothermic MP, 13.8% subnormothermic MP, and 16.9% utilized hypothermic oxygenated MP. The stringent documentation of ARRIVE elements concerning precise experimental execution, group size and selection, the choice of statistical methods, as well as adherence to the principles of the 3Rs, was notably lacking in the majority of publications, with less than 30% providing comprehensive details. Postoperative analgesia and antibiotics treatment were not documented in 82.1% of all included studies. None of the analyzed studies fully adhered to the ARRIVE Guidelines. In conclusion, the present study emphasizes the importance of adhering to reporting standards to promote reproducibility and adequate animal welfare in preclinical studies in machine perfusion. At the same time, it highlights a clear deficiency in this field, underscoring the need for further investigations into animal welfare-related topics.